Transbronchial fine needle aspiration biopsy and rapid on‐site evaluation in the setting of superior vena cava syndrome. Issue 4 (18th November 2011) - Brundyn, K.; Koegelenberg, C. F. N.; Diacon, A. H.; Louw, M.; Schubert, P.; Bolliger, C. T.; van den Heuvel, M. M.; Wright, C. A.
Abstract There is a paucity of prospective data on flexible bronchoscopy with rapid on‐site evaluation (ROSE) in the setting of superior vena cava (SVC) syndrome. The aims of this prospective study were to assess the diagnostic yield and safety of these investigations and specifically to evaluate the role of ROSE in limiting the need for tissue biopsies. Over a 5‐year period 48 patients (57.4 ± 9.7 years) with SVC syndrome secondary to intrathoracic tumors underwent flexible bronchoscopy with TBNA and ROSE. Endobronchial Forceps biopsy was reserved for visible endobronchial tumors with no on‐site confirmation of diagnostic material. ROSE confirmed diagnostic material in 41 cases (85.4%), and in only one of the remaining cases did the addition of a forceps biopsy increase the diagnostic yield (overall diagnostic yield of 87.5%). No serious complications were noted. The final diagnoses made included nonsmall lung cancer (n = 27), small cell lung cancer (n = 16), and metastatic carcinoma (n = 3). Two undiagnosed cases died of suspected advanced neoplasms (unknown primary tumors). We conclude that TBNA has a high diagnostic yield and is safe in the setting of SVC syndrome. With the addition of ROSE, tissue biopsy is required in the minority of cases. Diagn. Cytopathol. 2013;41:324–329. © 2011 Wiley Periodicals, Inc.